The potential of compounds isolated from Xylaria spp. as antifungal agents against anthracnose - Elias, Luciana M.; Fortlzamp, Diana; Sartori, Sergio B.; Ferreira, Marilia C.; Gomes, Luiz H.; Azevedo, Joao L.; Montoya, Quimi [UNESP]; Rodrigues, Andre [UNESP]; Ferreira, Antonio G.; Lira, Simone P. (Springer, 2018)
Anthracnose is a crop disease usually caused by fungi in the genus Colletotrichum or Gloeosporium. These are considered one of the main pathogens, causing significant economic losses, such as in peppers and guarana. The current forms of control include the use of resistant cultivars, sanitary pruning and fungicides. However, even with the use of some methods of controlling these cultures, the crops are not free of anthracnose. Additionally, excessive application of fungicides increases the resistance of pathogens to agrochemicals and cause harm to human health and the environment. In order to find natural antifungal agents against guarana anthracnose, endophytic fungi were isolated from Amazon guarana. The compounds piliformic acid and cytochalasin D were isolated by chromatographic techniques from two Xylaria spp., guided by assays with Colletotrichum gloeosporioides. The isolated compounds were identified by spectrometric techniques, as NMR and mass spectrometry. This is the first report that piliformic acid and cytochalasin D have antifungal activity against C. gloeosporioides with MIC 2.92 and 2.46 mu mol mL(-1) respectively. Captan and difenocona-zole were included as positive controls (MIC 16.63 and 0.02 mu mol mL(-1), respectively). Thus, Xylaria species presented a biotechnological potential and production of different active compounds which might be promising against anthracnose disease. (C) 2018 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda.
Keywords: 2-Hexylidene-3-methylbutanedioic acid; Amazon; Anthracnose; Plant pathogen